SISTEM INFORMASI PENERIMAAN SISWA BARU PADA SMAN 01 PASMAH AIR KERUH BERBASIS WEB - Andi Lala; Ryon Zeri Pranata (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2024)
Currently, information systems also have a huge influence, one of which is on the process of accepting new students at school. Acceptance of new students at school is defined as a place where students gain access to information to start further education. Currently, there are still many schools that do not use information systems technology to handle their problems. Such as the selection of outstanding students, environmental development students, and services when accepting new students, as well as the process of making reports, are all still manual. As happened at SMA 01 Pasmah Air Keruh, it was felt that the data collection processes were still not optimal and did not fully utilize information system technology. The system development method uses Rapid Application Development (RAD), system design uses DFD (Data Flow Diagram). The results of this research are that the system that has been built can be utilized by SMA N 01 Pasmah Air Keruh in carrying out promotions and accepting new students. Students who want to register don't need to bother coming to school, students just need to register via the new student admissions website that has been provided so it is faster and more efficient.